Seasonal changes in the gonadossomatic index, allometric condition factor and sex ratio of an auchenipterid catfish from eastern Amazonia - FREITAS, Tiago Magalhães da Silva (2014)
The aim of the present study was to evaluate the seasonal pattern of the gonadosomatic index (GSI), condition factor (K), and sex ratio in the catfish Auchenipterichthys longimanus (Siluriformes: Auchenipteridae) as an approach to identify its reproductive period. A total of 589 A. longimanus specimens (251 males and 338 females) were captured in the rivers of the Caxiuanã National Forest, in the Brazilian state of Pará, between July, 2008 and July, 2009. Among the male specimens, 171 were classified as adults and 80 as juveniles, while there were 249 adults and 89 juvenile females. Using a sinusoidal equation, analysis of the GSI revealed a reproductive asynchrony between the genders, with males attaining their highest GSI values in January, while females peaked in March. For males, the sinusoidal regression for GSI values was significant only when used the complete data set (P=0.001), wears no trend was identified for bimonthly means (P=0.136). For females, by contrast, significant values were obtained for both the complete data set (P=0.012) and bimonthly GSI means (P=0.026). For the condition factor, the sinusoidal equation returned significant seasonal variation in both raw data (P=0.02) and with mean values (P=0.00) for males, but only with raw data for females (P=0.04), which appears to reflect variation in the energy budget between genders. With regard to the sex ratio, more reproductive females were captured than males in January and March, 2009, which suggests a pattern of segregation related to the reproductive process. These parameters are fundamental to the assessment, protection, and management of natural fish stocks, as well as providing guidelines for the development of conservation strategies.